Use of Camel Rennet Extract: Manufacture of Mixed Fresh Cheese and its Quality - Bouras, Biya; Aissaoui-Zitoun, Ouarda; Benyahia, Férial Aziza; Djema, Souhila; Bouras, Leila; Zidoune, Mohammed Nassereddine; Felfoul, Imène (Food Science and Agriculture: Research Highlights Vol. 2, 2025)
To solve the problem of camel milk coagulation and to diversify the products based on this milk, this study targets the manufacture of fresh cheese by adding the goat milk to camel milk with 50% (v/v). The use of camel rennet extract as a bio-coagulant appears interesting in this milk mixture. The camel rennet was extracted from the abomasum of a 7-month-old dromedary. This extract in the freeze-dried form was recommended compared to the liquid form. The study of the optimisation of the quantity to be added to the mixed milk based on the cheese yield and texture was 0.2g/L. In addition, the use of a blend of mesophilic and thermophilic starter cultures was also recommended in the improvement of the acidification of the mixed milks. The quality of the fresh cheese obtained was approved at the physicochemical level by a good protein retention with 36.26 ± 1.75%/DM. Texture profile analysis revealed a cohesiveness of 0.32 ± 0.01 mm and a springiness of 14.25 ± 0.63 mm. The microstructure showed that the resulting cheese had numerous and large pores. FTIR analysis monitors the physicochemical composition, and X-ray diffraction analysis revealed a non-crystalline structure of the cheese. On the sensory scale, the panellists preferred the cheese coagulated with the freeze-dried camel rennet, with a score of 9/15. Finally, this study has proven the effectiveness of using camel rennet in cheese-making technology based on camel milk.